Hubungan Kausalitas Antara Jumlah Uang Beredar dan Tingkat Harga Di Indonesia. The Causality Relationship Between Money Supply and Consumer Price Index in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Studi Ilmu Keperawatan Fak. Kedokteran UGM, 2000)
This research aims to analyze the causal relationship between money supply and consumer price index in Indonesia. The data used here are quarterly time series data for the period of 1977.1 1997.2. Analysis is based on the Granger (1969, 1988 ) and Sims (1972) causality models accompained with the final prediction error to find optimal lag. The results of this research show there is an unidirectional causality between money supply and consumer price index where the changes of money supply cause the changes of consumer price index.